(untitled) (Indian Journal of Child Health, 2018)
Introduction: Oral health is fundamental to general health and well-being. A healthy mouth enables an individual to talk, eat, and socialize without experiencing active disease, discomfort, or embarrassment. Objectives: To assess the knowledge and oral hygiene practices of school children from both Government and Private schools in Mahabubnagar district. Materials and Methods: A total of 150 children aged 11–15 years were randomly selected from six Private and six Government schools. A questionnaire related to their personal and oral hygiene practices was distributed to the school children. Results: The results of this study showed thatmost respondents had a good knowledge of basic hygiene measures and positive attitude towards oral hygiene. The students of both schools exhibited poor oral hygiene practices but were significantly reported more in the Government school than in the Private schools (p<0.005). Majority of the respondents (91.3%) used a commercial toothbrush and toothpaste and half of them (50%) reported brushing twice a day. Two-third of the respondents (75%), had never visited a dental clinic. Conclusion: The results of the present study showed that the knowledge and oral hygiene practices of Government school children were less satisfactory in someaspects when compared to private school children.